Quantitative analysis of DNA levels in maternal plasma in normal and Down syndrome pregnancies - Hromadnikova, Ilona (BioMed Central, 2002)
BACKGROUND: We investigated fetal and total DNA levels in maternal plasma in patients bearing fetuses affected with Down syndrome in comparison to controls carrying fetuses with normal karyotype. METHODS: DNA levels in maternal plasma were measured using real-time quantitative PCR using SRY and β-globin genes as markers. Twenty-one pregnant women with a singleton fetus at a gestational age ranging from 15 to 19 weeks recruited before amniocentesis (carried out for reasons including material serum screening and advanced material age), and 16 pregnant women bearing fetuses affected with Down syndrome between 17 to 22 weeks of gestation were involved in the study. RESULTS: The specificity of the system reaches 100% (no Y signal was detected in 14 women pregnant with female fetuses) and the sensitivity 91.7% (SRY amplification in 22 of 24 examined samples). The median fetal DNA levels in women carrying Down syndrome (n=11) and the controls (n=13) were 23.3 (range 0–58.5) genome-equivalents/ml and 24.5 (range 0–47.5) genome-equivalents/ml of maternal plasma, respectively (P = 0.62). The total median DNA levels in pregnancies with Down syndrome and the controls were 10165 (range 615–65000) genome-equivalents/ml and 7330 (range 1300–36750) genome-equivalents/ml, respectively (P = 0.32). The fetal DNA proportion in maternal plasma was 0%-6 % (mean 0.8%) in women carrying Down syndrome and 0%-2.6 % (mean 0.7 %) in the controls, respectively (P=0.86). CONCLUSIONS: Our study revealed no difference in fetal DNA levels and fetal DNA: maternal DNA ratio between the patients carrying Down syndrome fetuses and the controls.